Associations between bio-motor ability, endocrine markers and hand-specific anthropometrics in elite female futsal players: a pilot study - Farhani, F.; Arazi, H.; Mirzaei, M.; Nobari, H.; Mainer-Pardos, E.; Chamari, I. M.; Baker, J. S.; Pérez-Gómez, J.; Chamari, K. (BMC Sports Science, Medicine and Rehabilitation, 2022)
The second-to-fourth digit ratio (2D:4D) has been calculated for individual athletes and sports, but it has not been investigated in futsal performance. Therefore, the aim of this study was to investigate any relationships between 2D:4D of the dominant and non-dominant hands and physical capacity performances, selected functional variables and hormone concentrations in elite female futsal players. Methods